2019
DOI: 10.1101/793976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using fluorescence flow cytometry data for single-cell gene expression analysis in bacteria

Abstract: Fluorescence flow cytometry is a highly attractive technology for quantifying single-cell expression distributions in bacteria in high-throughput. However, so far there has been no systematic investigation of the best practices for quantitative analysis of such data, what systematic biases exist, and what accuracy and sensitivity can be obtained. We here investigate these issues by systematically comparing flow cytometry measurements of fluorescent reporters in E. coli with measurements of the same strains in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…To estimate mean and variance we used a method that uses forward and side scatter to identify viable cells and fits the logfluorescence distribution by a mixture of a Gaussian and uniform distribution to remove possible outliers (e.g. contaminants, non-growing cells) Galbusera et al , 2019. Replicate measurements performed on different days were highly reproducible, with Pearson correlations R 2 > 0.99 for the mean between replicates in all conditions, and correlations for the variance ranging from R 2 = 0.85 to R 2 = 0.95 (Suppl. Fig.…”
Section: Noise Distribution Of Their Targets In Each Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate mean and variance we used a method that uses forward and side scatter to identify viable cells and fits the logfluorescence distribution by a mixture of a Gaussian and uniform distribution to remove possible outliers (e.g. contaminants, non-growing cells) Galbusera et al , 2019. Replicate measurements performed on different days were highly reproducible, with Pearson correlations R 2 > 0.99 for the mean between replicates in all conditions, and correlations for the variance ranging from R 2 = 0.85 to R 2 = 0.95 (Suppl. Fig.…”
Section: Noise Distribution Of Their Targets In Each Conditionmentioning
confidence: 99%
“…The Poissonian term, whose magnitude we denote by b c and is often referred to as the 'intrinsic noise' term, could in principle derive from intrinsic expression noise whose magnitude scales proportional to mean expression Taniguchi et al , 2010;Sánchez and Kondev, 2008. However, by comparing microscopy and flow cytometry measurements we have recently shown that, at these expression levels, the component b c derives almost entirely from the measurement noise of the flow cytometer Galbusera et al , 2019. As shown in Suppl.…”
Section: Noise Distribution Of Their Targets In Each Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] However, measurement errors in flow cytometry data inevitably arise from imperfect measurements, photon-counting statistics, and data storage methods. [14][15][16][17] Figure 1, borrowing from figure 1 in Galbusera et al, 17 illustrates data (such as the height, area, and width of a pulse) reported by a cytometer. To collect such data, one streams cells past a laser light source, and detects them via fluorescence picked up by detectors.…”
Section: Motivationsmentioning
confidence: 99%
“…This technology produces abundant data that can be used to infer cellular signaling networks 9‐13 . However, measurement errors in flow cytometry data inevitably arise from imperfect measurements, photon‐counting statistics, and data storage methods 14‐17 . Figure 1, borrowing from figure 1 in Galbusera et al, 17 illustrates data (such as the height, area, and width of a pulse) reported by a cytometer.…”
Section: Introductionmentioning
confidence: 99%